Differences in category information processing between areas TEO and TE of the macaque - Shimizu, Masaumi; Katakami, Shun; Okada, Masato; Sugase-Miyamoto, Yasuko; Hayashi, Kazuko; Matsuda, Keiji; Miura, Kenichiro; Eldridge, Mark A. G.; Saunders, Richard C.; Richmond, Barry J.; Matsumoto, Narihisa (Frontiers in Behavioral Neuroscience, 2025)
Object categorization is a fundamental visual function, via which primates group items based on perceptual similarity. Neurons that respond to a class of complex objects, such as faces, can be found in inferior temporal cortex of macaque monkeys, comprising areas TEO and TE. The ability of monkeys to categorize cat/dog images is greatly impaired when both TE and TEO are removed, but is only modestly impaired if either region is left intact. This suggests that both TE and TEO can support object categorization. We investigated what differences exist in category information processing between areas TEO and TE. For cat and dog stimulus images, we found that category decoding performance increased during the initial phase of a stimulus presentation, then remained stable in area TEO for the duration of the presentation in a passive fixation task. In area TE, category decoding performance continued to improve into later in the time window than in TEO. Furthermore, we found that, after cat/dog category training, area TE neuronal populations encode cat and dog category information more strongly than do TEO neurons even in a fixation task (Mann-Whitney U-test, p < 0.05). Together, our results suggest that area TEO processes category information without changing its representation, whereas the category information representation in area TE evolves over time (both within a trial and across category training sessions), indicating that responses in TE may be influenced by top-down feedback.